Influence of Service Quality and Price on Purchasing Decisions at PT Berkah Samudra Logistik Semarang - Hartiati, Anissa Sri Novira; Nurkhayati, Isnaini -; Paniya, Paniya - (Politeknik Negeri Semarang, 2023)
This research aims to identifying the effect of service quality and price on purchasing decisions at PT Berkah Samudra Logistik Semarang. Purposive sampling was implemented as a sampling technique for 55 respondents. The independent variables used in this study are Service Quality and Price. Meanwhile, the dependent variable used in this study is the Purchase Decision. Primary data collection using interviews and questionnaires, as well as literature studies for secondary data.”Validity test, reliability test, descriptive analysis, classic assumption test, multiple linear regression, t test, F test and coefficient of determination were chosen as the analytical method used in this study.